2023
DOI: 10.1038/s41598-023-33463-x
|View full text |Cite
|
Sign up to set email alerts
|

One to one comparison of cell-free synthesized erythropoietin conjugates modified with linear polyglycerol and polyethylene glycol

Abstract: With more than 20 Food and Drug Administration (FDA)-approved poly (ethylene glycol) (PEG) modified drugs on the market, PEG is the gold standard polymer in bioconjugation. The coupling improves stability, efficiency and can prolong blood circulation time of therapeutic proteins. Even though PEGylation is described as non-toxic and non-immunogenic, reports accumulate with data showing allergic reactions to PEG. Since PEG is not only applied in therapeutics, but can also be found in foods and cosmetics, anti-PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Comparative studies of LPG-, HPG-and PEG-anakinra bioconjugates showed that LPG conjugates exhibited significantly better proteolytic stability than their PEG analogues, and all conjugates significantly prolonged the elimination half-life of anakinra, with LPG and PEG conjugates prolonging it 4-fold compared to the unmodified protein. 15 Other bioconjugation studies were performed to compare the performance of LPG-and PEG-modified proteins (e.g., interleukin-4 WT, 16 interferon α2a, 17 and erythropoietin 18 ) in terms of their bioactivity. The PEGylated and PGylated forms of interleukin-4 WT and erythropoietin showed similar biological activities, whereas those of interferon α2a showed different pharmacokinetics.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparative studies of LPG-, HPG-and PEG-anakinra bioconjugates showed that LPG conjugates exhibited significantly better proteolytic stability than their PEG analogues, and all conjugates significantly prolonged the elimination half-life of anakinra, with LPG and PEG conjugates prolonging it 4-fold compared to the unmodified protein. 15 Other bioconjugation studies were performed to compare the performance of LPG-and PEG-modified proteins (e.g., interleukin-4 WT, 16 interferon α2a, 17 and erythropoietin 18 ) in terms of their bioactivity. The PEGylated and PGylated forms of interleukin-4 WT and erythropoietin showed similar biological activities, whereas those of interferon α2a showed different pharmacokinetics.…”
Section: ■ Introductionmentioning
confidence: 99%
“… 15 Other bioconjugation studies were performed to compare the performance of LPG- and PEG-modified proteins ( e.g. , interleukin-4 WT, 16 interferon α2a, 17 and erythropoietin 18 ) in terms of their bioactivity. The PEGylated and PGylated forms of interleukin-4 WT and erythropoietin showed similar biological activities, whereas those of interferon α2a showed different pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%